Kryzys pandemiczny w kontekście cofnięcia się procesów równościowych a zarządzanie kulturą płci (ZKP) = Pandemic crisis in the context of reversalof equality processes and gender culture management (GKM) - Stankiewicz, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Contemporary organizations are diverse in many respects, and one of the basic dimensions of diversity is gender. Within this division, many inequalities can be noticed, which have deepened during the pandemic, hinder the functioning of the organization, reduce its potential and become the cause of individual failures and dramas for women.
Keywords: różnorodność; polityka równościowa; kultura organizacyjna; zarządzanie różnorodnością; zarządzanie kulturą płci; przywództwo; język inkluzyjny; diversity; equality policy; organizational culture; diversity management; gender culturemanagement; leadership; inclusive language